Resolvamos problemas de combinación - Oloya Manrique, Edgar Overson (2020)
This sufficiency work has been prepared for children from the second grade of primary education of the Educational Institution "Santiago Apóstol" of the city of Bagua Grande in 2019, with the theme entitled: "Let's solve problems three times a number of developthe Solve Problems of Quantity competition. In the elaboration of the session we have worked with the teaching processes of the area of Mathematics and with the capacity Communicates your Understanding on Numbers and Operations.The strategies were used to promote the active and meaningful participation of all students, especially underpinned by the Problem Resolution approach. _x000D_ It is intended at all times to the arouse student's interest and motivation for Mathematics since it is an area that develops skills such as: Development of logical thinking in children to reason in an orderly manner, prepares the mind for thinking